Flexible real‐time skin dosimeter based on a thin‐film copper indium gallium selenide solar cell for electron radiation therapy. Issue 4 (16th January 2023) - Shin, Dong‐Seok; Kim, Tae‐Ho; Rah, Jeong‐Eun; Lee, Se Byeong; Lim, Young Kyung; Jeong, Jonghwi; Kim, Haksoo; Shin, Dongho; Son, Jaeman
Abstract: Purpose: Various dosimeters have been proposed for skin dosimetry in electron radiotherapy. However, one main drawback of these skin dosimeters is their lack of flexibility, which could make accurate dose measurements challenging due to air gaps between a curved patient surface and dosimeter. Therefore, the purpose of this study is to suggest a novel flexible skin dosimeter based on a thin‐film copper indium gallium selenide (CIGS) solar cell, and to evaluate its dosimetric characteristics. Methods: The CIGS solar cell dosimeter consisted of (a) a customized thin‐film CIGS solar cell and (b) a data acquisition (DAQ) system. The CIGS solar cell with a thickness of 0.33 mm was customized to a size of 10 × 10 mm 2 . This customized solar cell plays a role in converting therapeutic electron radiation into electrical signals. The DAQ system was composed of a voltage amplifier with a gain of 1000, a voltage input module, a DAQ chassis, and an in‐house software. This system converted the electrical analog signals (from solar cell) to digital signals with a sampling rate of ≤50 kHz and then quantified/visualized the digital signals in real time. We quantified the linearity/ sampling rate effect/dose rate dependence/energy dependence/field size output factor/reproducibility/curvature/bending recoverability/angular dependence of the CIGS solar cell dosimeter in therapeutic electron beams. To evaluate clinical feasibility, we measured the skin point doses by attaching the CIGS solar cell to an anthropomorphic phantom surface (for forehead, mouth, and thorax). The CIGS‐measured doses were compared with calculated doses (by treatment planning system) and measured doses (by optically stimulated luminescent dosimeter). Results: The normalized signals of the solar cell dosimeter increased linearly as the delivered dose increased. The gradient of the linearly fitted line was 1.00 with an R‐square of 0.9999. The sampling rates (2, 10, and 50 kHz) of the solar cell dosimeter showed good performance even at low doses (<50 cGy). The solar cell dosimeter exhibited dose rate independence within 1% and energy independence within 3% error margins. The signals of the solar cell dosimeter were similar (<1%) when penetrating the same side of the CIGS cell regardless of the rotation angle of the solar cell. The field size output factor measured by the solar cell dosimeter was comparable to that measured by the ion chamber. The solar cell signals were similar between the baseline (week 1) and the last time point (week 4). Our detector showed curvature independence within 1.8% (curvatures of <0.10 mm − ) and bending recovery (curvature of 0.10 mm −1 ). The differences between measured doses (CIGS solar cell dosimeter vs. optically stimulated luminescent dosimeter) were 7.1%, 9.6%, and 1.0% for forehead, mouth, and thorax, respectively. Conclusion: We present the construction of a flexible skin dosimeter based on a CIGS solar cell. Our findings demonstrate that the CIGS solar cell has a potential to be a novel flexible skin dosimeter for electron radiotherapy. Moreover, this dosimeter is manufactured with low cost and can be easily customized to various size/shape, which represents advantages over other dosimeters.